Implementasi Pembelajaran Berdiferensiasi dalam Meningkatkan Pemahaman Peserta Didik pada Pelajaran Pendidikan Agama Islam - Jannah, Eneng Raudhatul; Fuad, Ai Fatimah Nur (Sekolah Tinggi Agama Islam Sumatera Medan, 2024)
Currently, learning often imposes global demands, so it does not adjust to the interests and needs of students. For this reason, differentiated learning is offered. This learning is oriented towards teaching methods that optimize the needs of students. Differentiated learning has three strategies 1) content 2) process 3) product. With regard to that, this study aims to analyze the strengths in the differentiated learning process for students at SDN Kertajaya 03 grade 4. The research method chosen is qualitative which explores the phenomenon studied in words, the data collected in the form of prmer and secondary data, through observation, interviews, and documentation studies. Primary data sources were collected from teachers and students while secondary from photos and documents. The results of the study showed a change in the level of understanding of students. The strength is in the process that makes it easier for students because it matches their interests, talents and profiles. This research certainly has implications for learning evaluation, so that it can be followed up to improve more optimal learning outcomes, especially in Islamic religious education lessons.